PENGARUH EARNING PER SHARE (EPS) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM - Mega Kurnia; Ade Fauji; Aria Cendana Kusuma (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
The purpose of this study is to determine the effect of Earning Per Share (EPS) and Debt to Equity Ratio (DER) on stock prices either partially or simultaneously in manufacturing companies in the consumer goods industry sub-sector of food and beverages. This study uses a quantitative approach with secondary data in the form of Earning Per Share (EPS) and Debt to Equity Ratio (DER) data and stock prices. Determination of the sample in this study was using purposive sampling technique with 3 criterias in order to obtain 9 companies from 29 companies. The analysis technique used is panel data regression analysis technique using the help of the Eviews10 application. The results of data processing show that the data is normally distributed after data transformation and there are no symptoms of classical assumptions in the study. The conclusion obtained in the research shows that Earning Per Share (EPS) partially has a positive and significant effect on stock prices. Debt to Equity Ratio (DER) partially has no effect on stock prices. Earning Per Share (EPS) and Debt to Equity Ratio (DER) simultaneously have a positive and significant effect on stock prices